Eksistensi Ruh Perspektif Syekh Nawawi Al Bantani (Analisis Penafsiran Syekh Nawawi Al Bantani Dalam Tafsir Marah Labid Likasyfi Ma’na Al-Qur’an Al Majid) (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
Mining knowledge from Sheikh Nawawi Al Bantani's monumental work in the interpretation of Marah Labid will never cease, including the theme of the soul as discussed in this article. This writing aims to present Sheikh Nawawi's perspective on the meaning of the soul in his interpretative work, which is characterized by mystical elements with a distinctive Nusantara flavor. The approach taken involves analytical descriptions of the meaning of the soul, followed by a critical analysis and comparison with other interpreters. From Sheikh Nawawi Al Bantani's interpretation of the eloquence of the meaning of the "Rûh" in the Qur'an, it can be generally understood that the term "ruh" encompasses the concept of something that gives creatures the ability to live (soul). Additionally, it can mean the angel Gabriel or even the Qur'an, signifying mercy and assistance from Allah. As the soul is abstract and holds implicit meanings, the deeper it is explored, the richer its significance becomes. Therefore, this research is conducted to contribute to the world of interpretation, providing insights into the existence of the soul.